Nutritional values of traditional open-pollinated melon (Cucumis melo L.) and watermelon (Citrullus lanatus [Thumb]) varieties - Szamosi, Cs.; Némethy-Uzoni, H.; Balázs, G.; Stefanovits-Bányai, É. (International Journal of Horticultural Science, 2007)
The aim of our experiments was to investigate the internal quality parameters of some old melon and watermelon landraces or varieties whether they have any desirable characteristics. Measurements were carried out using 8 different types of melon (Cucumis melo L.) and 8 accessions of watermelon (Citrullus lanatus [Thumb]), which were self pollinated under greenhouse conditions. Besides the determination of dry matter content; soluble solids, titratable acidity of the fruit juices, investigation of carbohydrates, total phenol content was measured by spectrophotometer. Total antioxidant capacities were determined spectrophotometrically using the FRAP method. We found some accesions both among melon and watermelon varieties, which could be characterized by outstanding inner content.